2022
DOI: 10.3934/agrfood.2022003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drought stress on growth, biochemical changes and leaf gas exchange of strawberry (<i>Fragaria</i> × <i>ananassa</i> Duch.) in Indonesia

Abstract: <abstract> <p>Drought stress is one of the challenges that can affect the growth and the quality of strawberry. The study aims to determine the growth, biochemical changes and leaf gas exchange of three strawberry cultivars under drought stress. This study was conducted in a glasshouse at Indonesian Citrus and Subtropical Fruits Research Institute, Indonesia, from July-November 2018. The experiment was arranged in a factorial randomized completely block design (RCBD) with three replications and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…The result was consistent with the study done by Zhang et al [ 76 ] on soybean. The reduction of leaf area under water deficit stress was also previously reported in many plants such as wheat cultivars [ 77 ], marigold plants [ 56 ], and strawberries [ 65 , 78 ]. Drought stress reduced leaf area by 51.6% during the vegetative stage of cowpea due to the inhibition of cell growth [ 79 ].…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…The result was consistent with the study done by Zhang et al [ 76 ] on soybean. The reduction of leaf area under water deficit stress was also previously reported in many plants such as wheat cultivars [ 77 ], marigold plants [ 56 ], and strawberries [ 65 , 78 ]. Drought stress reduced leaf area by 51.6% during the vegetative stage of cowpea due to the inhibition of cell growth [ 79 ].…”
Section: Resultssupporting
confidence: 67%
“…This reduction in pigment content was previously reported in several crop plants, including bread wheat [ 117 ], sorghum [ 3 ], millet [ 118 ], red chili varieties [ 119 ], and different sunflower varieties [ 70 ]. Others [ 65 , 120 , 121 ] also found that lower water field capacity tends to decrease total chlorophyll in chamomile, strawberries, and peanut plants, respectively. The reduction may be because of the low activity of the photosynthetic elements under stress.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Fresh biomass of the body plant, 80-95% is the embrace of water, which plays an animated role in diverse physiological processes, including numerous aspects of plant growth, metabolism, and development [37]. Water deficit is one of the challenges that can impact the plant growth and biochemical change [38,39,40]. Plants produce oxidative stress directly or indirectly under drought conditions, and it is one of the master diverse of plant response, resulting in altered membrane integrity, cell membrane damage, biochemical and physiological alterations which lastly change the proactive of plant [41,42,43], because the strong correlation between growth and availability of water, cells are enlargement more affected by decreased water compared to cell division [44].…”
Section: Growth Parametersmentioning
confidence: 99%